The legal aspects of the intellectual formation in Polish ecclesiastical seminaries - Adamiak, Stanisław (Prawo Kanoniczne, 2024)
The article describes the legal framework for the higher education of the candidates for priesthood in Polish seminaries. The relevant legal acts, both ecclesiastical and civil, have been cited. The author shows that at the moment all Polish seminarians are officially enrolled as the university students at the Polish theological faculties. However, several legal difficulties arise from such solution, especially with regard to the faculties at the state universities, which have to follow all the regulations of the 2018 Law on Higher Education. Therefore, the postulated solutions are either moving all the seminarians to the university cities (which is easily feasible given their shrinking numbers) or basing the whole system on the purely ecclesiastical institutions.